اثر اللغة العربية في ازالۃ التناقضات الظاھرۃ بین الآیات القرآنیۃ: دراسة جھود الآلوسی فی"روح المعانى" : Effect of Arabic language in resolving apparent contradictions in the Qur’ānic Verses: A Study of al-Ālūsī’s efforts in “Rūḥ al-Maʻānī” - Muhammad Ramzan; Dr. Syed Hamid Farooq Bukhari; Dr Muhammad Shahbaz Manj (Al-Qamar, 2018)
In order to resolve the apparent contradictions of the Qur’ānic verses, the commentator often has to use the Arabic language and its rules. Naḥw, Ṣarf, Ishtiqāq, Maʻānī, Bayān, Badīʻ etc. are of great importance in this regard. The present paper, highlighting the effect of Arabic language in overcoming the apparent contradictions, explores the renowned commentator of the Quran al-Ālūsī’s efforts in his widely celebrated commentary of the Quran named “Rūh al-Maʻānī”. It finds that the learned commentator, on many occasions, has successfully used the Arabic language and its referred principles to dispel the illusion of contradiction between the Qur’ānic verses.